Analysis of Factors Influencing the Implementation of a Balanced Nutrition Diet in Male Santri at the Maesan Mojo Islamic Boarding School, Kediri Regency - Jian Bagas Wara S; Panca Radono (Universitas STRADA Indonesia, 2024)
Efforts so that one's nutritional needs can be obtained optimally is by organizing food which is managed by applying scientific disciplines such as nutrition, management, dietetics and carried out by applying the principles of efficiency and effectiveness because the aim of organizing food is to produce food of good quality and in accordance with needs. Attention to the provision of food for students at Islamic boarding schools for youth is very important. The purpose of this research is to study the factors that influence a balanced nutritional diet at the Maesan Mojo Islamic Boarding School, Kediri Regency. Quantitative research method with a cross-sectional approach and chi- square analysis of data. The population in the study were 117 male students and 85 samples were used. Retrieval of data by accidental sampling, namely researchers taking samples that happened to be encountered at that time.The results of the study on the characteristics of respondents with the highest prevalence were aged 15 years with the last education being junior high school and found the influence of nutritional knowledge, physical activity, type of food with a balanced nutritional diet supported by p-values of 0.002 and 0.000. The discussion in this study is that there are factors that influence a balanced nutritional diet, namely nutritional knowledge, physical activity and types of food which are interrelated. This is evidenced by the results of the research analysis that has been carried out. The conclusion of the study is the discovery of factors that influence balanced nutrition in adolescents including age, knowledge of nutrition, physical activity, type of food.